Microstructure of boiled yam (Dioscorea spp.) and its implication for assessment of textural quality - Otegbayo, B.; Aina, J.; Asiedu, Robert; Bokanga, M. (Wiley, 2005)
The effects of boiling on the microstructure of yams and their association with the textural quality of “boiled yam,” arguably the most common food product from yams, were studied using six varieties with variable cooking qualities from each of the two species, Dioscorea alata L. and D. rotundata Poir. Histological studies on raw yams showed parenchyma cells of both species to be three‐dimensional and polyhedral in shape, with starch granules loosely arranged in D. rotundata but densely packed in D. alata. Generally, there was cell separation and rounding off of cells in cooked yams of D. rotundata varieties, whereas cell separation was only partial with no rounding off in D. alata. Mealy boiled yams showed complete cell separation and the “rounding off” phenomenon, whereas the waxy ones showed partial retention of textural cell integrity. These relative changes in microstructure of yam when boiled could serve as indicators of textural quality in boiled yam.